PENGARUH GROWTH OPPORTUNITY, PROFITABILITY, BUSINESS RISK DAN SIZE TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Property dan Real Estate Yang Terdaftar Di BEI Periode 2009-2017) - Ashop Barqoya (universitas Pamulang, 2019)
The purpose of this study was to determine the effect of growth opportunity, profitability, business risk, and size on the company's capital structure either partially or simultaneously.The object of research used is the property and real estate sector companies listed on the Indonesia Stock Exchange in 2009-2017. This study uses a purposive sampling technique in determining research samples. the number of companies selected as the study sample were 18 companies registered in the property and real estate sector. This study uses a quantitative approach. The results showed that partially growth opportunity and size had not significant effect, while profitability and business risk had a significant effect on capital structure. the results of testing simultaneously growth opportunity, profitability, business risk, and size have a significant influence on the capital structure.